Assessing the impact of minimum temperature on crop over Winter season in northwest mountain areas of Vietnam - Kham, Duong Van; Quyen, Nguyen Huu (VNU Journal of Science: Earth and Environmental Sciences, 2012)
Abstract. This report shows the method for assessing minimum temperature effecting on probability of plant growth over the winter in the northwest mountain region of Vietnam by useing Gumbel distribution. This method determines the beginning and ending of critical temperature threholds based on ENSO scenarios. Thence, safe periods are defined for plant in the research region. The results show that: In El Nino year, safe period is longer than in La Nina year. Keywords : Minimum temperature, Critical temperature threshold, beginning and ending date of T n <T c , safety day.